Wharton’s jelly tissue cryopreservation for efficient mesenchymal stromal/stem cell retrieval - Obushko, Ruslana; Trufanova, Natalia; Revenko, Olena; Petrenko, Oleksandr (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):231